2016
DOI: 10.5380/rmu.v3i3.47840
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes De Transporte Terrestre Envolvendo Veículos Automotores No Estado Do Paraná

Abstract: . We registered the amount and the type of accident, the day of week and the period of day when the events occurred, and the amount, sex, age, and clinical condition of the victims. RESULTS: In the period studied there were 248.805 transport accidents. Cars and motorcycles accounted for the majority of vehicles involved. The accidents occurred mainly on weekends and during the periods of afternoon and evening. These accidents resulted in 307.916 victims. The typical profile were young males. The injuries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In Brazil, around 20,000,000 motorcycles are registered, and in Santa Catarina State, the study venue, there are around 800,000 motorcycles. Such a high number of motorcycles also increases the cases of traffic accidents 2 . A study on traffic accidents involving motorcycles between 2001 and 2010, observed an increase of 327% in deaths and 620% of hospital expenses with hospitalizations of injured motorcyclists, despite the legislation demands minimum safety and comfort conditions for motorcycle users 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, around 20,000,000 motorcycles are registered, and in Santa Catarina State, the study venue, there are around 800,000 motorcycles. Such a high number of motorcycles also increases the cases of traffic accidents 2 . A study on traffic accidents involving motorcycles between 2001 and 2010, observed an increase of 327% in deaths and 620% of hospital expenses with hospitalizations of injured motorcyclists, despite the legislation demands minimum safety and comfort conditions for motorcycle users 3,4 .…”
Section: Introductionmentioning
confidence: 99%